2017
DOI: 10.1007/978-3-319-52522-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons and Challenges in Land Change Modeling Derived from Synthesis of Cross-Case Comparisons

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policyIf you believe that this document breaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…Moreover, Pijanowski et al (2002) reported that even when 10 predictor variables were used on 100-m pixel resolution in the Land Transformation Model to assess future urban expansion, the model's prediction ability was 46% [81]. Furthermore, by comparing 13 applications of 9 different popular peer-reviewed land change models, Pontius et al (2018) proved that, for 6 of the 13 models, the ratio of the intersection of the observed change and predicted change to the union of the observed change and predicted change was less than 0.15 [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Pijanowski et al (2002) reported that even when 10 predictor variables were used on 100-m pixel resolution in the Land Transformation Model to assess future urban expansion, the model's prediction ability was 46% [81]. Furthermore, by comparing 13 applications of 9 different popular peer-reviewed land change models, Pontius et al (2018) proved that, for 6 of the 13 models, the ratio of the intersection of the observed change and predicted change to the union of the observed change and predicted change was less than 0.15 [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are three main stream approaches for LUC models: models which rely primarily on economic models and data [17][18][19], models that rely equally on multiple approaches and data to determine cause and effect relationships [20][21][22] and models that are role-based analyses, where a norm is established to allocate LUC-related impacts [23][24][25][26].The objectives of the present paper are: firstly, to use three reference land use maps of the Elaionas catchment for the years 1979, 1996 and 2007 in the Land Transformation Model (LTM) [27,28], so as to forecast the urban sprawl for the year 2027; secondly, based on both the recorded land use changes and the future urban sprawl scenarios developed by the LTM, to examine the effects of current and future urban expansion on the design hydrograph, and, thirdly, to estimate the impact of urban sprawl on the associated sediment yield generated by the latter storm events.The Land Transformation Model (LTM) used for forecasting future LUC was created by the Human-Environment Modelling and Analysis Laboratory of Purdue University [28] and is based on the coupling of an Artificial Neural Network (ANN) with a Geographic Information System (GIS), in which the latter was used to provide the inputs for the ANN. Although there are many machine learning models such as extreme learning machine, support vector machine, adaptive neuro-fuzzy inference system and deep learning models the ANN was selected in this study because the LTM predefined tool box is broadly used worldwide so as to forecast land use evolution [29]. These inputs are used to train and test the neural network in order to generate a numerical solution between the input and the output, expressed as a future urban area prediction map for the year 2027.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both single and multiresolution techniques were used [48,49]. The multiresolution evaluation has been suggested in the literature but has seldom been used [50]. The key distinction between single resolution and multiresolution approaches is that the latter is forgiving of near misses.…”
Section: Validationmentioning
confidence: 99%
“…At present, China and Russia participate in extensive strategic cooperative activities, such as political and economic activities, with complementary advantages and win-win collaborations. Under the background of the "Belt and Road" initiative of China, the Russian Eurasian Economic Alliance and the Mongolian Prairie Silk Road strategy, the Irkutsk region is becoming a key node city for the construction of the China-Mongolia-Russia Economic Corridor [17]. The study period is during the hot and short summer in Russia when the air is dry and there are few clouds and low precipitation.…”
Section: Overview Of the Study Areamentioning
confidence: 99%